2021
DOI: 10.1186/s13075-021-02621-9
|View full text |Cite|
|
Sign up to set email alerts
|

Proteoglycan-4 is an essential regulator of synovial macrophage polarization and inflammatory macrophage joint infiltration

Abstract: Background Synovial macrophages perform a multitude of functions that include clearance of cell debris and foreign bodies, tissue immune surveillance, and resolution of inflammation. The functional diversity of macrophages is enabled by distinct subpopulations that express unique surface markers. Proteoglycan-4 (PRG4) is an important regulator of synovial hyperplasia and fibrotic remodeling, and the involvement of macrophages in PRG4’s synovial role is yet to be defined. Our objectives were to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Angiogenin (ANG) is an angiogenic protein also described as anti-bacterial protein secreted by macrophages ( 26 ). Proteoglycan-4 (PRG4) is mainly expressed by fibroblast-like cells but serves as an important regulator of inflammation ( 27 ) and has been described to act as an essential regulator of synovial macrophage polarization and inflammatory macrophage joint infiltration ( 28 ). Biotinidase has been described to be essential for basic macrophage functions.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenin (ANG) is an angiogenic protein also described as anti-bacterial protein secreted by macrophages ( 26 ). Proteoglycan-4 (PRG4) is mainly expressed by fibroblast-like cells but serves as an important regulator of inflammation ( 27 ) and has been described to act as an essential regulator of synovial macrophage polarization and inflammatory macrophage joint infiltration ( 28 ). Biotinidase has been described to be essential for basic macrophage functions.…”
Section: Discussionmentioning
confidence: 99%
“…PRG4 has been shown to bind CD44 ( Al-Sharif et al, 2015 ) (and inhibit HA stimulated signaling ( Sarkar et al, 2019 )), and more recently MMP9 ( Menon et al, 2021 ) (which associates with CD44 as well ( Yu and Stamenkovic, 1999 )). Given PRG4’s anti-inflammatory ( Qadri et al, 2018 ; Das et al, 2019 ; Menon et al, 2021 ; Krawetz et al, 2022 ), immunomodulatory ( Qadri et al, 2021 ; Krawetz et al, 2022 ), and anti-fibrotic properties ( Qadri et al, 2020 ; Krawetz et al, 2022 ), it is intriguing to consider what type of additive, synergistic, or inhibitory biological properties TSG-6 bound PRG4 might have in various tissues and diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Our in vivo observations should be rationalized in the context of our recent discoveries regarding PRG4’s role in tissue macrophage homeostasis and function. We have recently shown that in Prg4 GT/GT mice, the synovial microenvironment skews the balance of resident macrophages towards a pro-inflammatory M1 phenotype with age-dependent progressive decline in the numbers of anti-inflammatory wound-healing macrophages ( 51 ). Furthermore, macrophages from Prg4 GT/GT animals had reduced anti-inflammatory interleukin-10 (IL-10) expression at baseline and in response to TLR2 ligand stimulation ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that in Prg4 GT/GT mice, the synovial microenvironment skews the balance of resident macrophages towards a pro-inflammatory M1 phenotype with age-dependent progressive decline in the numbers of anti-inflammatory wound-healing macrophages ( 51 ). Furthermore, macrophages from Prg4 GT/GT animals had reduced anti-inflammatory interleukin-10 (IL-10) expression at baseline and in response to TLR2 ligand stimulation ( 51 ). Extending these findings to our peritoneal model, it is plausible to expect that the impaired expression of IL-10 in Prg4 GT/GT mice contributed to the lack of adequate resolution of inflammation ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation